2017
DOI: 10.1089/pancan.2017.0006
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein/Albumin Ratio and Prognostic Nutritional Index Are Strong Prognostic Indicators of Survival in Resected Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: We evaluated the clinical importance, such as the occurrence of postoperative pancreatic fistula (POPF) or prognosis, of preoperative serum markers of chronic inflammation, nutrition, and immunity, as well as that of serum tumor markers after curative resection of pancreatic ductal adenocarcinomas (PDACs).Methods: Between 2006 and 2015, 43 patients with PDACs underwent curative resection at Tottori Prefectural Central Hospital. We analyzed which preoperative indicators (i.e., C-reactive protein/albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A further 14 studies were excluded, as 5 were single-arm studies, 2 evaluated postoperative values, and the remaining 7 included patients who did not have pancreatic cancer resection. Therefore, 8 retrospective comparative studies [20][21][22][23][24][25][26][27] were deemed appropriate for inclusion (Figure 1). The included studies reported a total of 1056 patients undergoing pancreatic cancer resection, of whom 378 belonged to the high CAR group and the remaining 678 belonged to the low CAR group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A further 14 studies were excluded, as 5 were single-arm studies, 2 evaluated postoperative values, and the remaining 7 included patients who did not have pancreatic cancer resection. Therefore, 8 retrospective comparative studies [20][21][22][23][24][25][26][27] were deemed appropriate for inclusion (Figure 1). The included studies reported a total of 1056 patients undergoing pancreatic cancer resection, of whom 378 belonged to the high CAR group and the remaining 678 belonged to the low CAR group.…”
Section: Resultsmentioning
confidence: 99%
“…Although the use of neoadjuvant chemotherapy was comparable between the high and low CAR groups in each study, there was significant heterogeneity among the included studies. Murakawa et al [22] and Ikeguchi et al [25] reported no use of neoadjuvant chemotherapy in their included patients. Oshima et al [20] reported the use of neoadjuvant chemotherapy in all patients included.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Elevated preoperative CAR values have been shown to be a strong, independent predictor of poor prognosis after pancreatic adenocarcinoma resection, but exceedingly few studies have assessed if CAR is a viable screening or diagnostic marker for the development of CR-POPF. 11,12 Further, only Sakamoto et al 13 has directly compared CAR to the current standard for CR-POPF screening, POD 1 DAC.…”
Section: Introductionmentioning
confidence: 99%